Democratizing Risk Governance Bridging Science, Expertise, Deliberation and Public Values - Gattinger, Monica (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This open access book features contributions from a multidisciplinary team of leading and emerging scholars focused on democratization of risk assessment, management, and communication. The volume identifies and sheds light on key risk governance dilemmas related to public trust, risk perception and public participation. The first part of the book articulates the relationship among science, expertise, deliberation and public values, featuring an in-depth analysis of the concept of 'motivated reasoning,' and the role of trust, values and worldviews in understanding and addressing contemporary controversies over risk decision-making. The volume's second part features eight case studies from three policy fields - energy, genomics, and public health - and a special section dedicated to vaccine decision-making for Covid-19. Chapters analyze the level, nature and mechanisms of public involvement in risk decision-making, assessing its contribution to the effectiveness and legitimacy of decisions. The case studies focus predominantly on Canada, but they draw on global scholarship and are of direct relevance for scholars and practitioners of risk governance in any country. Monica Gattinger is Director of the Institute for Science, Society and Policy, Full Professor at the School of Political Studies and Founding Chair of Positive Energy at the University of Ottawa. Dr. Gattinger is an award-winning researcher and highly sought-after speaker, adviser and media commentator in the energy and arts/cultural policy sectors. Her innovative research programme convenes business, government, Indigenous, civil society and academic leaders to address complex policy, regulatory and governance challenges. She has published widely in the energy and arts/cultural policy fields, with a focus on strengthening decision-making in the context of fast-past technological change and markets, changing social values, and fluctuating levels of trust in governments, industry, science and expertise. Gattinger is Fellow at the Canadian Global Affairs Institute, board member of the Clean Resource Innovation Network, and serves on advisory boards for the Institute on Governance, the National Research Council Canada, the Nuclear Waste Management Organization, Pollution Probe and the University of Calgary. Monica received the 2020 Clean50 Award for her thought leadership in the energy sector. She holds a Ph.D. in public policy from Carleton University.